2021
DOI: 10.1001/jamanetworkopen.2020.36512
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Co-occurrence of Alcohol, Nicotine, and Other Substance Use Disorder Diagnoses Among US Transgender and Cisgender Adults

Abstract: Key Points Question What is the prevalence of substance use disorder diagnoses (SUDDs) among US transgender and cisgender adults? Findings In this study of 15 637 transgender and 46 911 cisgender adults, transgender adults had a significantly higher prevalence of nicotine, alcohol, and drug SUDDs than cisgender adults. Meaning In this study, transgender adults experienced elevated levels of SUDD relative to their cisgender peers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 50 publications
3
67
2
2
Order By: Relevance
“…In our study, the prevalence of consumption was higher, while in the other study, the age of consumption onset was earlier in the transgender group, often in the early stages of adolescence [50]. These data, which point to greater vulnerability of the group as the result of the discrimination they are subjected to, tended to homogenise in adulthood because of the increased concern for health and a desire to stop consuming among this population [51]. Of note, when we considered tobacco use disorder in this current study, we found no differences between the transgender and cisgender groups, although the small number of studies included in this analysis meant that our confidence in the reliability of this result was poor.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In our study, the prevalence of consumption was higher, while in the other study, the age of consumption onset was earlier in the transgender group, often in the early stages of adolescence [50]. These data, which point to greater vulnerability of the group as the result of the discrimination they are subjected to, tended to homogenise in adulthood because of the increased concern for health and a desire to stop consuming among this population [51]. Of note, when we considered tobacco use disorder in this current study, we found no differences between the transgender and cisgender groups, although the small number of studies included in this analysis meant that our confidence in the reliability of this result was poor.…”
Section: Discussioncontrasting
confidence: 52%
“…The most unexpected result of this present study was that there were no differences in the probability of presenting alcohol use or alcohol use disorder between cisgender and transgender people. In contrast, previous studies have postulated that one of the toxic substances with the greatest presence among the transgender population is alcohol [46,51,56]. Indeed, 60.4% of this population reported consuming alcohol regularly, and 24.3% reported having drunk excessively in the last 30 d [70].…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, we did not examine study objectives by gender as gender identity was not assessed in the parent study. Gender influences risks for SUD ( 7 ) and poor sleep ( 33 ), and gender minority individuals are a high-risk population for SUD ( 39 ). Next, recruitment for the parent study was aimed at composing a “real world” SUD sample.…”
Section: Discussionmentioning
confidence: 99%
“…TGD populations regularly report increased violence and discrimination, particularly among trans people of color [17], including fears and experiences with discrimination in healthcare settings [18]. In the face of stigma and violence, substance use remains a health concern facing TGD populations [19,20]. These complex factors contribute to health disparities leading to negative outcomes among individuals in this high-risk group.…”
Section: Introductionmentioning
confidence: 99%